Cross-border effects of restructuring, including change of legal form : proceedings of a seminar held in Munich, Germany, in 2000 during the 54th Congress of the International Fiscal Association /: proceedings of a seminar held in Munich, Germany, in 2000 during the 54th Congress of the International Fiscal Association. (2016) - Unknown
No abstract available